(untitled) (CAHIERS MAGELLANES-NS, 2024)
Urban areas increasingly serve as the hubs for technological advancement, economic expansion, and human activity. But growing urbanization also brings forth an array of complex challenges, the most significant of which is the impact of climate change. These difficulties are especially noticeable in India, where rapid urbanization and growing vulnerability to the consequences of climate change coexist. This research study explores the complex interplay of climate change, urbanization, risk, resilience, and vulnerability within cities. This study investigates how the notion of smart cities presents novel approaches to address climate-related hazards and foster urban adaptability. It also outlines the significance of resilience in urban planning. It analyses a few case studies that present real-world resilience-building initiatives in urban settings. The concept of Smart Cities and the fundamental components that underpin their existence, such as technology, data, and connectivity, are also discussed while highlighting their innovative potential. It seeks to thoroughly examine the experiences of Ahmedabad, aiming to illuminate the potential for smart cities to address the challenges posed by climate change and urbanization in India's changing environment. It comprehensively analyses Ahmedabad's difficulties while acknowledging and celebrating its ambitions, inventive solutions, and capacity to adapt amid an unpredictable climate outlook.